2013
DOI: 10.1007/s12199-013-0339-5
|View full text |Cite
|
Sign up to set email alerts
|

Association of ambient air pollution and meteorological factors with primary care visits at night due to asthma attack

Abstract: Aim The association of outdoor air pollution and meteorological elements with primary care visits at night due to asthma attack was studied. Methods A case-crossover study was conducted in a primary care clinic in Himeji City, Japan. The subjects were 956 children aged 0-14 years who visited the clinic with an asthma attack between the hours of 9 p.m. and 6 a.m. Daily concentrations of particulate matter, ozone, nitrogen dioxide, and a number of meteorological elements were measured, and a conditional logistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 20 publications
2
26
1
1
Order By: Relevance
“…However, we did find evidence that ozone may be associated with PCVs due to asthma attack. Our previous study (n = 174) also found no association between PM 2.5 and PCVs among children in the 2010/2011 or 2011/2012 winters in the same setting [2]. Our present sample size (n = 112) was smaller than that in our previous study, and insufficient statistical power might accordingly be a limitation.…”
Section: Discussioncontrasting
confidence: 67%
See 2 more Smart Citations
“…However, we did find evidence that ozone may be associated with PCVs due to asthma attack. Our previous study (n = 174) also found no association between PM 2.5 and PCVs among children in the 2010/2011 or 2011/2012 winters in the same setting [2]. Our present sample size (n = 112) was smaller than that in our previous study, and insufficient statistical power might accordingly be a limitation.…”
Section: Discussioncontrasting
confidence: 67%
“…In a Japanese study, Yamazaki et al [9] found an association between ozone and PCVs due to asthma attack in the summer but not during the winter. In contrast, Yamazaki et al [2] found no stable association between ozone and PCVs in another study. We could not explain the reason of the uncertainty of the association.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…The nature of associations reported from past studies of asthma morbidity and temperatures have not been consistent, likely due to differences in climate, study design and statistical methodology. Some studies have found positive associations between temperatures and asthma admissions,23 24 some have reported negative associations,2 5 7 8 16 19 25 26 while a few have reported significant associations with high and low temperatures 6 27. The seasonal differences in associations of RH with asthma hospitalisations observed in this study, negative association in the cold season and positive in the hot season, have not been commonly reported in previous studies.…”
Section: Discussionsupporting
confidence: 42%
“…Despite the fact that many previous studies have reported associations between high temperatures and asthma morbidity,6 23 24 27 the direct biological mechanisms by which high temperatures cause asthma exacerbations are still unclear. A recent study suggested that the pulmonary c-fibre sensory nerve plays an important role in asthma in hot temperatures 47.…”
Section: Discussionmentioning
confidence: 99%